Portobiliary Fistula in a Liver Transplant Recipient Treated With an Endoscopically Deployed Fully Covered Self-Expandable Biliary Metal Stent. Issue 5 (May 2019) - Murray, Fritz; Buetikofer, Simon; Dutkowski, Philipp; Gubler, Christoph
Abstract : ABSTRACT: Biliary complications following liver transplantations, with leaks and bile duct strictures being the most common ones, are greatly feared. Portobiliary fistulas are rare, but may cause potentially life-threatening complications. The presented case shows the first successful treatment of a portobiliary fistula by an endoscopically deployed fully covered self-expandable metal stent after liver transplantation. In accordance to the already established use in refractory bile leaks, we believe that fully covered self-expandable metal stent is a safe and efficient treatment option for portobiliary fistula.